PERIZINAN USAHA MIKRO, KECIL, DAN MENENGAH (UMKM): BENTUK PEMBERDAYAAN, PERLINDUNGAN HUKUM DAN MEWUJUDKAN NEGARA KESEJAHTERAAN - Ahmad Redi; Luthfi Marfungah; Rayhan Fiqi Fansuri; Michelle Prawira; Agatha Lafentia (Jurnal Muara Ilmu Sosial, Humaniora, dan Seni, 2022)
The existence or presence of micro, small and medium enterprises (“UMKM”) has an economic, social, and political impact. Goods or services produced from UMKM activities have economic value and are cheap. UMKM has advantages, one of which is having a strategic role in dealing with the ups and downs of the economy in Indonesia. Licensing is needed to guarantee the business activities of UMKM actors. Licensing is very important for UMKM players considering the increasingly global business competition and currently entering the process of economic liberalization. It is clear in Government Regulation Number 7 of 2021 concerning Ease, Protection, and Empowerment of Cooperatives and Micro, Small and Medium Enterprises, that in order to increase national economic growth, empowerment and licensing of UMKM is needed. The method used in this paper is normative juridical. The legal issue that will be examined in this paper is regarding the licensing of UMKM that provide legal protection and create a welfare state. UMKM licensing as a form of legal protection has an important value and has an impact, namely the business becomes legal, is provided with legal assistance, is used for capital applications with the aim of improving the quality and quantity of products and being able to compete with products from within and outside the country, access to business assistance from the government, and empowerment or supervision from the government so as to create a welfare state.